PEMAHAMAN MASYARAKAT TERHADAP KEBERADAAN KESATUAN PENGELOLAAN HUTAN PRODUKSI (KPHP) MODEL TEBING TINGGI DI KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Muhammad Tabrani; Rudianda Sulaeman; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Kepulauan Meranti Regency is one of regency in Riau Province, that expansion of Bengkalis Regency. Wide area of Meranti Archipelago Regency is 3.707,84 km2 with forest region 345.442,42 ha. Impact of the value population growth, illegal logging, unilateral land conversion of secondary swamp forest and forest fire result pressure for forest region and wooded area that remained. Forest Management Unit Production (FMUP) Tebing Tinggi was formed base on central government policies of Kepmenhut No. SK.343/Menhut-II/2011 about Region Consisting of FMUP Model Tebing Tinggi (Unit XXIV) in Kepulauan Meranti Regency Province Riau, with wide area 69.747 ha that consist of protected forest 412 ha and limited forest production 69.335 ha. By that forming of FMUP Model Tebing Tinggi in Kepulauan Meranti Regency, should to know how public understanding of FMUP Model Tebing Tinggi existence. This research is conducted to analyze understanding level and public responses of FMUP Model Tebing Tinggi existence. Data collected by using survey method trought observation stages, interview and literature study. Analyze that used is descriptive analyze. The result of this research show that public understanding level of FMUP Model Tebing Tinggi existence still low. According responses by 78,34% public of Tanjung Darul Takzim Village and 88,34% public of Sungai Tohor Village agree if forest managed by FMUP Model Tebing Tinggi. Keywords : Understanding, public, forest management unit production